The Outcome of Endoscopic Transethmosphenoid Optic Canal Decompression for Indirect Traumatic Optic Neuropathy with No-Light-Perception - Bo Yu; Yingjie Ma; Yunhai Tu; Wencan Wu (Journal of Ophthalmology)
Purpose. To present the safety and effect of endoscopic transethmosphenoid optic canal decompression (ETOCD) for indirect traumatic optic neuropathy (ITON) patients with no-light-perception (NLP). Methods. A retrospective study performed on 96 patients (96 eyes) with NLP after ITON between June 1, 2010, and June 1, 2015, who underwent ETOCD, was reviewed. Visual outcome before and after treatment was taken into comparison. Results. The overall visual acuity improvement rate after surgery was 46.9%. The improvement rates of visual acuity of patients who received treatment within 3 days of injury, 3–7 days after injury, and later than 7 days were 63.6%, 42.9%, and 35.7%, respectively. Statistically significant difference was detected between the effective rates of within-3-day group and later-than-7-day group (χ2=5.772, P=0.016). The effective rate of atrophy group and nonatrophy group was 25.0% and 51.3%, respectively. The effective rate was significantly higher in nonatrophy group (χ2=4.417, P=0.036). Conclusion. For patients suffering from ITON with NLP, time to medical treatment within 3 days is an influential factor for visual prognosis. Optic nerve atrophy is an important predictor for visual prognosis. Treatment should still be recommended even for cases of delayed presentation to hospital.